Comparison of two types of vertically aligned ZnO NRs for highly efficient polymer solar cells. Issue 4 (27th November 2012) - Gonzalez‐Valls, Irene; Angmo, Dechan; Gevorgyan, Suren A.; Sebastián Reparaz, Juan; Krebs, Frederik C.; Lira‐Cantu, Monica
Abstract Vertically aligned ZnO nanorods (NR) are prepared by two different syntheses methods and applied on polymer solar cells (PSCs). The ZnO electrodes work as the electron transport layer with the P3HT:PCBM blend acting as the active material. Several organic blend solution conditions are optimized: concentration, solvent, and deposition speed. The effect of different NR electrode morphologies is analyzed on the solar cell performance and characterized by current–voltage curves and IPCE analyses. The photovoltaic performance of the solar cells was observed to be influenced by many factors, among them infiltration of the organic P3HT:PCBM blend within the ZnO NR layer. The infiltration of the active layer was monitored by cross section SEM and energy dispersive X‐ray spectroscopy analyses. Our results show that higher power conversion efficiencies are achieved when shorter NRs lengths are applied. The best power conversion efficiency obtained was 2.0% for a 400 nm ZnO NR electrode. © 2012 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys, 2013